Підсистема управління заявками абітурієнтів до університету - Боцюра, А. С. (ХНУРЕ, 2023)
The process of joining the university can be stressful and take a lot of time, both from students and from university supporters. The elements of the system allow the applicant to be more informed about the choice of the educational program